Global Transportation of Foodstuffs - Piala, Peter; Galierikova, Andrea; David, Andrej (Communications - Scientific letters of the University of Zilina, 2017)
Maritime transport belongs to the modes of transportation which ensures intercontinental transport of passengers and cargo between the continents. Not only it is very effictive, but it also enables to carry a huge volume of cargo. The transportation of temperature controlled cargo started in the 19th century with the transportation of meat. Until then, transportations of goods under the influence of the temperature were realised only between regions. It is necessary to care about proper handling, cooling, packaging and the compatibility during the transportation of temperature-controlled cargo.